An association of cavernous angioma, multiple aneurysms and azygos anterior cerebral artery -Case report - Takayama, Shokei; Handa, Jyoji; Matsumura, Kenichi; Matsuda, Masayuki; Kidooka, Minoru (Japanese Journal of Stroke, 1986)
A case harboring cavernoma, azygos anterior cerebral artery (azygos ACA) and multiple aneurysms is reported. A 68-year-old female was admitted with subarachnoid hemorrhage (SAH). Neurological examination showed mild confusion, moderately severe headache and severe neck stiffness. CT scan demonstrated SAH which was most prominent in the frontal interhemispheric fissure. Bilateral carotid angiography demonstrated an azygos ACA and two aneurysms, one at the distal end of the azygos ACA and the other in the proximal end of it. Tumor stain, early venous filling, or dilated abnormal vessels were not demonstrated. At operation, a hematoma in the interhemispheric fissure extending from the right frontal lobe was evacuated. Three, instead of angiographically suspected two, aneurysms were found. One was found to arise at the site of take-off of the pericallosal artery from the azygos ACA. It was apparently unruptured, and was successfully clipped. There were two more unruptured aneurysms, one on a small branch of the azygos ACA and the other on the left proximal ACA (A1). Both were sessile in type. They were reinforced by cottonoid sheet (Bem-sheet). Histological examination of a mass found in the clot revealed cavernoma. Postoperative course was uneventful. Coexistence of arteriovenous malformation and cerebral aneurysm is not uncommon, but that of cavernoma and aneurysm has not been reported previously. In the present case, SAH was secondary to rupture of the cavernoma, which was not found at preoperative angiography and CT. The present case stresses that it is necessary to take into account the possibility of the presence of angiographically occult vascular lesion even in patients with SAH where aneurysm has been recognized.